A hydrogen-bonded channel structure formed by a complex of uracil and melamine - Thomas, Reji; Kulkarni, G. U. (Beilstein Journal of Organic Chemistry, 2007)
The structure of a 1:1 complex of uracil and melamine obtained by cocrystallization has been investigated. The structure involves hydrogen bonded layers with apertures stacked along the a and b directions giving rise to channels, unlike the complex of cyanuric acid with melamine.